2004
DOI: 10.1182/blood-2003-12-4355
|View full text |Cite
|
Sign up to set email alerts
|

IL-2–induced CD4+ T-cell expansion in HIV-infected patients is associated with long-term decreases in T-cell proliferation

Abstract: Administration of interleukin 2 (IL-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 39 publications
(42 reference statements)
0
70
1
1
Order By: Relevance
“…139 The somewhat paradoxical effect of IL-2 may be explained by the increase of distinct CD4CCD25C expressing high level of FOXP3, defined as cytokine-induced na€ ıve (CEN) T-cells, which could act as T regulatory cells with suppressor activity. [140][141][142][143] IL-7 is another key cytokine which role is impaired in HIV infection, mostly thank to impairment of receptor signaling via CD127 (a component of IL-7 receptor [IL-7R]). [144][145] IL-7 is crucial for T cell development and homeostasis thanks to its anti-apoptotic and co-stimulatory proliferative signals 146 and in untreated patients with HIV infection high levels of IL-7 reflects a compensatory loop mechanism to contrast HIV-induced lymphopenia (Fig.…”
Section: New Treatment Strategies and Immunotherapy In Aging Hiv Patimentioning
confidence: 99%
“…139 The somewhat paradoxical effect of IL-2 may be explained by the increase of distinct CD4CCD25C expressing high level of FOXP3, defined as cytokine-induced na€ ıve (CEN) T-cells, which could act as T regulatory cells with suppressor activity. [140][141][142][143] IL-7 is another key cytokine which role is impaired in HIV infection, mostly thank to impairment of receptor signaling via CD127 (a component of IL-7 receptor [IL-7R]). [144][145] IL-7 is crucial for T cell development and homeostasis thanks to its anti-apoptotic and co-stimulatory proliferative signals 146 and in untreated patients with HIV infection high levels of IL-7 reflects a compensatory loop mechanism to contrast HIV-induced lymphopenia (Fig.…”
Section: New Treatment Strategies and Immunotherapy In Aging Hiv Patimentioning
confidence: 99%
“…In NOD type-1 diabetic mice, IL-2 can prevent or reverse autoimmunity, by stimulation of Tregs (Grinberg-Bleyer, Baeyens et al). In infectious diseases, HIV infected patient IL-2 treatment induces an increase of thymic export (Carcelain, Saint-Mezard et al 2003) and induces a peripheral CD4 T cell expansion by limiting CD4 proliferation and increasing CD4CD25+ subset (Sereti, Anthony et al 2004). To prevent the effects of aging homeostatic deregulation and TCR repertoire alterations, we tested the effect of IL-2 or transfer of regulatory T cells (CD4+CD25+) injected in middleaged B6 mice (15-month old) (Figure 8).…”
Section: Prevention Of Aging and Immunodepressionmentioning
confidence: 99%
“…Among HIV infected individuals cytokine trial interventions have shown that introduction of exogenous recombinant IL-2 restores the ability of the immune system to induce T cell expansions especially the CD4 + moiety [72]. As such, the degree of HIV-associated immune activation that is mirrored by T-cell turnover is reduced among recombinant IL-2 recipients [73]. These events show that IL-2 functions to control deleterious immune effects of HIV.…”
Section: Cytokines In Hivmentioning
confidence: 99%